Effect of Addition of Non-Ionic Surfactant to the A2l(III)-Morin Complex in Spectrophotometry Determination of Aqueous Aluminum(III) - Suah, FBM; Ahmad, M; Heng, LY (Univ Kebangsaan Malaysia, 2024)
The effect of surfactants on the Al(III)-morin complex have been studied. It was found that non-ionic surfactant noticeably enhances the absorbance of the Al(III)-morin complex. Determination of submicrogram quantities of Al(III) ion at pH4.00 was made possible by the addition of triton X-100. Maximum absorption was obtained at wavelength of 425 nm, with the calculated molar absorptivity, epsilon e, of 9.31 x 10(3) l. mol(-1). cm(-1). A linear calibration curve of 0.03 to 2.0 mu g mL(-1) with the detection limit of 0.015 mu g mL(-1) was attained for determination of Al(III) ion. The calculated relative standard deviation (r.s.d) was 2.2% for Al(III) ion quantified at 1.0 mu g mL(-1). The influence of foreign ions towards the Al(III)-morin complex responses have been carried out too, with Cu(II), Zn(II) and Pb(III) were found to be the main interferences.